THE EFFECT OF HERBAL ESSENTIAL OIL IN PRESERVATIVE SOLUTION, ON QUANTITATIVE, VASE LIFE, BACTERIA-INDUCED STEM XYLEM BLOCKAGE OF LISIANTHUS VAR. ECHO - Porianejad, Farzane; Hasanzadeh, Nader; Kalatejarei, Sepideh (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2014)
In this study the effect of essential oil taken from medicinal plant as antibacterial components in preservative solution of Lisianthus var. Echo (Eustoma grandiflorum) was investigated. The test was done with application of preservative solution. Â Cut flowers were treated with different concentrations of Thyme (Thymus vulgaris), Spearmint (Mentha spicata) and Lavender (Lavandula officinalis) essential oil in addition to Sucrose 2.5%. The results showed that there was the longest time in vase life with Thyme in 50 ppm (15.6 days) and the control treatment showed the shortest vase life (11.6 days). Moreover, Thyme with 50 ppm had the highest effect on relative fresh weight and solution uptake. In addition, bacteria-induced stem xylem blockage, extracted from the end of stem, was cultured in NA medium culture with several concentrations of essential oil. The result showed that in pure concentration (100%) inhibition was completed and in various concentrations of essential oil the bacterial population was reduced.Keywords: essential oil, lavender, preservative solution, spearmint, thymeÂ